Implementasi Bantuan Hukum Pro Bono dan Pro Deo Dalam Penegakan Hukum di Indonesia - Nurhidayati Nurhidayati; Maharani Maharani; Fauziah Lubis (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
Law exists in people's lives with the aim of creating justice, order and peace in society where the law applies, the State clearly emphasizes through legislation that every citizen is seen as equal before the law and has the right to equality in legal protection. However, in reality, people with low economic status, or because of their ignorance, are unable to feel the protection and protection of the law in order to fight for justice, this is contrary to the principle of a rule of law, namely demanding guarantees of equality before the law . This research belongs to normative legal research (normative juridical), research using primary legal materials accompanied by secondary legal materials. A statutory approach is used in this study to analyze all related arrangements. In this study will discuss issues regarding implementation and related legal arrangements. The findings in this study indicate that there is an obligation for law enforcers to be able to provide maximum and equitable legal services for all levels of society, be it free legal assistance, pro bono case handling, or pro deo proceedings. The next finding is that there are sanctions for law enforcers who refuse to carry out these obligations. Keywords: Legal Aid, Pro Bono obligations, Pro Deo obligations.